Bottom‐Up Synthesis of MeSx Nanodots for Optoelectronic Device Applications. Issue 11 (29th July 2016) - Van Le, Quyet; Nguyen, Thang Phan; Park, Minjoon; Sohn, Woonbae; Jang, Ho Won; Kim, Soo Young
Abstract : WSx and MoSx nanodots are synthesized from (NH4 )2 WS4 and (NH4 )2 MoS4 precursors using a solvothermal method, and applied to organic photovoltaic cells (OPVs) and organic light emitting diodes (OLEDs) as hole injection layers (HILs). The optical band gaps of WSx and MoSx nanodots are 3.55 and 3.1 eV, respectively, and these nanodots show their strongest photoluminescence (PL) emission at 438 and 436 nm. The work functions of the nanodots increased from 4.3–4.4 to 5.0–5.1 eV following ultraviolet/ozone (UVO) treatment. By sandwiching thin layers of UVO‐treated WSx and MoSx as HILs, the power conversion efficiency of OPVs dramatically increases from 1.51% to 3.0% and 2.95%, comparable to that of poly(3, 4 ethylenedioxythiophene):poly(styrene‐sulfonate) (PEDOT:PSS) based devices (3.23%). This increased OPV efficiency is believed to come from the increased work function, large band gap, and PL properties of nanodots. The UVO‐MoSx based OLED shows a higher maximum luminance efficiency (14.7 cd A −1 ) compared to PEDOT:PSS based devices (13.1 cd A −1 ). In addition, this study confirms that the stabilities of the OPV and OLEDs in air can be prolonged by using UVO‐treated WSx or MoSx nanodots as HILs. These results demonstrate the great potential of synthesized WSx or MoSx nanodots for use as HILs in optoelectronic devices. Abstract : WSx and MoSx nanodots are synthesized from (NH4 )2 WS4 and (NH4 )2 MoS4 precursors using a solvothermal method, and applied to organic photovoltaic cells (OPVs) and organic light emitting diodes (OLEDs) as hole injection layers (HILs). The stabilities of the OPV and OLEDs in air can be prolonged by using ultraviolet/ozone‐treated WSx or MoSx nanodots as HILs.